Analysis of the 5S Principles in Forming a Safety Culture at MI Muhammadiyah 1 Kradenan - Susanti, Elina; Habibah Jannah, Nur Baety (Proceeding International Conference on Religion, Science and Education, 2025)
Safety Culture has not been a concern in certain companies and institutions including educational institutions. The 5S principle (Seiri, Seiton, Seiso, Seiketsu, Shitsuke) is one of the work principles originating from Japan that can be applied as a foundation for safety culture. This study aims to analyze the implementation of 5S in every facility and infrastructure in MI Muhammadiyah 1 Kradenan. The type of research used is qualitative descriptive with data collection techniques are observation, interviews and documentation. The results of the study prove that the 5S principle in forming a safety culture in MI Muhammadiyah 1 Kradenan has been optimal in the application of the 5S principle, there is a sorting of facilities and infrastructure that are not suitable for use because they are feared to endanger school residents, and are taken to the Muhammadiyah multipurpose building in Kradenan village, this fulfills the principle of seiri. The principle of seiton neatness in MI Muhammadiyah 1 Kradenan has been maintained and all school members are orderly in using the facilities that have been used; seiso in terms of cleanliness at MI Muhammadiyah 1 Kradenan there is a picket schedule to clean the classroom and surrounding area and community service is held once a month on Friday by all school residents to avoid diseases that can be caused by the environment; seiketsu for school cleanliness standards, there are many posters to remind school residents to keep the school environment clean and tidy; shitsuke to ensure the quality of facilities and infrastructure is maintained once a year a meeting is held to evaluate the operations of MI Muhammadiyah 1 Kradenan. The results of this study can be used as insight into safety culture and can be a reference for other educational institutions in implementing 5S.